FAKTOR DUKUNGAN ORANG TUA TERHADAP PRESTASI ATLET PENCAK SILAT PSHT RANTING MOJOSARI MOJOKERTO TAHUN 2026 - Muhammad Bachtiar; Septyaning Lusianti; Moh.Nur Kholis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The success of pencak silat athletes is influenced not only by mastery of techniques and physical condition, but also by environmental support, especially parental involvement through emotional, informational, instrumental, and assessment support that can strengthen motivation, discipline, and enthusiasm for training and competing. This study focuses on analyzing the influence of parental support on the achievements of Pencak Silat athletes from PSHT Ranting Mojosari Mojokerto in 2026 using a quantitative approach and quantitative descriptive design. The study involved all parents of PSHT Ranting Mojosari athletes as the population, with 30 respondents determined using a saturated sampling technique. Data were collected through a Likert-scale questionnaire, then analyzed using validity tests, reliability tests, descriptive analysis, normality tests, linearity tests, and simple linear regression tests assisted by SPSS 25. Data distribution shows that parental support is in the moderate category at 63.3% and athlete achievement is in the moderate category at 66.6%. The regression analysis yielded a significance value of 0.000 (p < 0.05), a correlation coefficient (R) of 0.987, and a determination coefficient (R²) of 0.975, confirming the positive and significant influence of parental support on athlete achievement, contributing 97.5%, while 2.5% was influenced by other factors outside the study. These findings indicate that increased parental support is in line with increased athlete achievement, so family involvement needs to be strengthened in the sports coaching process.